Comparative Analysis of Direct Pressure and Electrocauterization Techniques for Hemorrhage Control in the Liver Bed during Laparoscopic Cholecystectomy - Dharmoon Arija; Syed Moin Islam Shah; Saiqa Rafiq; Nida Ahmed; Abdul Salam Memon; Nazia Naseer (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: This research examines the effectiveness of applying direct pressure and utilizing electrocoagulation to reduce liver bed hemorrhage after laparoscopic cholecystectomy, which is widely regarded as the gold standard for treating symptomatic gallstones. While this surgical approach offers benefits such as less pain and faster recovery, challenges like liver bed bleeding remain a concern, particularly in cases involving cholecystitis. cholecystectomy Study design: Randomized controlled study Duration and place of study: This study was conducted in Gulam Muhammad Mahar Medical College Hospital Sukkur from March 2024 to March 2025 Methodology: This randomized controlled trial was carried out in the Department of General Surgery, involving Objective: To determine the efficacy of direct pressure application and electrocoagulation in controlling bleeding from the liver bed following laparoscopic 130 patients aged 18 to 60 years who experienced liver bed hemorrhage following laparoscopic cholecystectomy. To address the bleeding, participants were 1071| International Journal of Pharmacy Research & Technology | Jan - May 2025 | Vol 15 | randomly assigned to receive either Laparoscopic cholecystectomy is widely electrocoagulation (Group A) or direct pressure application. If the initial interventions were ineffective, alternative or advanced hemostatic treatments were employed, with open cholecystectomy performed if necessary. Exclusion criteria included ASA ≥3, obstructive jaundice, cirrhosis, bleeding disorders, and liver or renal dysfunction. Data analysis was conducted using SPSS version 23.0, with statistical significance set at p<0.05. Results: A total of 130 patients participated in this study, divided into two groups of 65 each. Group A consisted of patients receiving electrocoagulation, while Group B included those undergoing direct pressure application. All participants were aged between 18 and 60 years, with an average age of 49.3 years in Group A and 40.0 years in Group B. The mean body mass index (BMI) was 25.2 kg/m² for Group A and 25.5 kg/m² for Group B. Both genders were represented in the study, although the majority participants in each group were female. of Conclusion: Electrocoagulation is more effective than direct pressure application for preventing bleeding in the liver bed.